(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In case of acute obstructive cholecystitis, percutaneous transhepatic microcholecystostomy (PTMCS) was performed in 38 patients. Developed tactical principles for minimally invasive treatment of acute complicated cholecystitis, based on early clinical sonographic and intraoperative diagnosis, stages of minimally invasive treatment using ultrasound-guided microcholecystostomy, laparoscopic and mini-accessible cholecystectomy with drainage of the common bile duct and endoscopic papilosphincterotomy allow us to individualize tactical and therapeutic approaches for acute complicated cholecystitis.